(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The study was conducted to know the relative abundance of insect pests and their predators on 5 boro rice varieties namely Arize tez, Teea, Sakti, Sathi and BRRI Dhan 28. In Arize Tez variety, short horned grasshopper revealed the highest percent relative abundance (87.25%) at tillering stage and green rice leafhopper was only at panical initiation stage. Among insect predators, wasp showed the highest percent relative abundance (33.33%) both at tillering and panical initiation stages. In Teea variety, the highest percent relative abundance of short horned grasshopper was recorded at tillering (80.21%) and panicle initiation (86.03%) stages while spider and lady bird beetle had 21.05% at tillering stage, wasp (21.05% and 40.00%), damselfly (21.05% and 40.00%) at tillering and panical initiation stages, respectively. In Sakti variety, short horned grasshopper had the highest percent relative abundance (72.54% and 69.05%) at tillering and panicle initiation stages while dragonfly had 30.77% at tillering, wasp had 30.77% and 66.66% at tillering and panicle initiation stages. In Shathi variety, the highest percent relative abundance of short horned grasshopper was recorded at tillering (59.46%) and panicle initiation (52.27%) stages while wasp (41.67%) at panical initiation stage. In variety BRRI dhan 28, the highest percent relative abundance of insect pests was recorded in short horned grasshopper (76.73% and 86.05%) both at tillering and panicle initiation stages while in insect predators, wasp had 40% at tillering and 50% at panicle initiation stages but dragonfly had 50% only at panicle initiation stage. Bangladesh J. Agril. Res. 43(1): 81-88, March 2018